The use of a Corophium volutator chronic sediment study to support the risk assessment of medetomidine for marine environments. (25th February 2014) - Fox, Michelle; Ohlauson, Cecilia; Sharpe, Alan D.; Brown, Rebecca J.
Abstract Chronic sediment studies were conducted using the marine amphipod Corophium volutator as part of an environmental risk assessment of the novel antifouling compound medetomidine. Two studies were performed, starting with neonates of less than 7 d old. A 28‐d study considered endpoints of survival and growth (length and wet wt) and a 76‐d study looked at survival, growth (length and wet wt), and reproduction (number of gravid females and neonates). Medetomidine was dosed via the sediment at nominal test concentrations of 1.0 µg/kg, 3.2 µg/kg, 10 µg/kg, 32 µg/kg, and 100 µg/kg (dry wt). In the 28‐d growth study, a significant increase in mortality was observed at 32 µg/kg and 100 µg/kg. In the 76‐d reproduction study, there were significant adverse effects on survival (32 µg/kg and 100 µg/kg), growth (100 µg/kg), and reproduction (100 µg/kg). The overall lowest‐observed‐effect concentration was 32 µg/kg medetomidine. For this test substance the increased study duration did not increase the overall sensitivity of the test. The present study suggests that the predicted sediment environmental concentration (PECsediment) of 0.003 µg/kg for medetomidine would not be expected to cause adverse effects on the life history of C. volutator. Environ Toxicol Chem 2014;33:937–942. © 2014 SETAC